Analogies related to the content-conceptual amount of substance in high school Chemistry textbooks (Research, Society and Development, 2022)
The analog reasoning has been widely used for the development of scientific concepts, especially in the 19th century. In the context of Chemistry teaching, analogical language has been used as a resource to ease the teaching and learning of abstract Chemistry concepts. However, the specialized literature indicates that the use of analogies, if not applyed properly, can generate epistemological obstacles. In this context, the present work evaluated the use of analogies used to approach school content and the amount of substance in Chemistry textbooks published in different periods. From the comparative study between the works, we observed advances in the quality of the analogies used in the explanation of the content-conceptual amount of substance and its unit, the mole. The results showed that this language resource is a great instrument for the construction of knowledge, but also, if used in a non-systematized way, analogies can cause distortions in the understanding of scientific content. The study allows a discussion of didactic content from which professors can be instrumentalized regarding the proper use and importance of analogical relationships in scientific literacy.